Lattice relaxations around impurities in metals - P.H. Dederichs; N. Papanikolaou; N. Stefanou; R. Zeller (Novel Materials-Design and Properties, 1998)
We review first-principles calculations of the size effect in dilute transition-metal alloys. The calculations apply local density functional theory and a Green's function method based on the KKR multiple-scattering formalism. In each cell, the full anisotropic potential in included and the forces on the atoms are calculated by the Hellmann-Feynman theorem. The method is applied to predict the atomic positions around d+sp impurities in Cu and Al. The results compare favorably with experimental data from extended X-ray-absorption-fine-structure and lattice-parameter measurements.